The Effect of Educational E-Booklets on Prospective Newlyweds' Knowledge Level about Stunting Prevention - Ayu, Ella Kusuma Ning; Setyarini, Didien Ika; Marcelina, Sheila Tania; Wulandari, Lisa Purbawaning (Universitas Aisyah Pringsewu, 2023)
Background: Stunting is a serious problem in fetuses and children up to the age of two, as it can increase infant mortality rates, morbidity, developmental disorders, and lead to low adult productivity. Stunting occurs due to a lack of knowledge about stunting prevention, starting from the preconception period. Therefore, counseling and education for prospective newlyweds are essential components in improving knowledge. This study aimed to determine the effect of educational e-booklet media on the knowledge of prospective newlyweds regarding stunting prevention at the Office of Religious Affairs in the Bululawang District. Methods: The research design used in this study was pre-experimental with a One Group Pre-Test Post-Test approach, involving 30 prospective newlyweds who met the inclusion criteria and were selected through simple random sampling. Data were collected by administering research questionnaires before and after providing educational media. Results: Bivariate analysis using the Wilcoxon Signed Rank Test showed that there was an effect of educational e-booklet media on the improvement of knowledge about stunting prevention among prospective newlyweds (p-value less than 0,05). Therefore, health education on stunting prevention needs to be provided for prospective newlyweds.